From the History of Contract Cheating to the New Challenges of Artificial Intelligence: The Changing Landscape of Academic Integrity (Canadian Perspectives on Academic Integrity, 2023)
We present the second issue of the fifth volume of the Canadian Perspectives on Academic Integrity (CPAI). This issue features the third invited historical article about contract cheating and three peer-reviewed articles that highlight two challenging issues within the field of academic integrity--mental health and artificial intelligence--and a study that explores the definition of academic misconduct, which is a persistent challenge in higher education.